From job search to hiring and promotion: The labour market experiences of ethnic minorities in Beijing - Hasmath, R (2011)
Drawing on micro-level census data and interviews with individual workers and employers, this article examines the job-search, hiring and promotion experiences of ethnic minority workers and jobseekers in Beijing. Labour market data indicate that ethnic minorities are at a disadvantage relative to the dominant Han ethnic group, particularly when it comes to employment in high-wage, skilled jobs. The evidence provided here suggests this may be attributable to gaps in the institutional framework that encourage reliance on social-network capital for job search, hiring and promotion. © The author 2011. Journal compilation © International Labour Organization 2011.